A late Fammenian age storm-dominated succession at Berrocal (Iberian Pyrite Belt - Spain) - Fernandes, Paulo (2014)
The Berrocal area is situated in the northern limb of Valverde del Camino anticlinal in the Spanish sector the Iberian Belt and exposes the upper part of the Phyllite-Quartzite Group. Recent studies on palynostratigraphy and sedimentology of the Berocal section indicates that the stratigraphic succession is late Famennian age (VH miospore biozone) and was accumulated on the offshore zone of a siliciclastic shelf dominated by storm events.